Orthostatic haemodynamics may be impaired in frailty. - ROMERO-ORTUNO, ROMAN; KENNY, ROSE; LAWLOR, BRIAN (My University, 2011)
Background: orthostatic hypotension (OH) is a physical sign that reflects a final common pathway of various forms of disordered physiology, which is the hallmark of geriatric frailty. Fried et al. recognise three increasing frailty phenotypes in older people, based on measurements of weight loss, exhaustion, grip strength, walking speed and physical activity. Orthostatic haemodynamics have not been considered as markers of frailty in older people. Objective: to classify a community sample of older people into three increasing frailty phenotypes and compare their orthostatic haemodynamics. Design: cross-sectional study. Setting: geriatric research clinic. Subjects: a total of 442 subjects (mean age 72, 72% females) without dementia or risk factors for autonomic neuropathy. Methods: the sample was classified according to modified Fried criteria. Orthostatic systolic blood pressure (SBP), diastolic blood pressure (DBP) and heart rate (HR) responses were monitored during an active stand with Finometer?. Results: one hundred and ninety-eight subjects (44.8%) were classified as non-frail, 213 (48.2%) as pre-frail, and 31 (7.0%) as frail. Across groups, there was a significant increasing gradient in baseline HR (P = 0.008) and decreasing gradients in Delta HR (i.e. maximum HR within 30 s?baseline HR) (P < 0.001) and maximum HR by 30 s (P < 0.001). On average, by 30 s after stand, non-frail subjects had recovered 98% of their baseline SBP, while pre-frail and frail subjects had recovered 95 and 92%, respectively (P for trend = 0.064). Conclusions: the orthostatic HR response and, to a lesser extent, SBP recoverability, appear impaired in frailty. Orthostatic haemodynamics may be useful markers of frailty.
PUBLISHED
Keywords: Gerontology; orthostatic hypotension (OH); Ageing